GaN Schottky barrier photodiode on Si (1 1 1) with low-temperature-grown cap layer - Chuah, Lee Siang; Z., Hassan; H., Abu Hassan; Naser Mahmoud, Ahmed (Elsevier B.V., 2009)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home